Nanostructured Lipid Carrier Gel Formulation of Recombinant Human Thrombomodulin Improve Diabetic Wound Healing by Topical Administration - Yuan-Shuo Hsueh; Yan-Jye Shyong; Hsiu-Ching Yu; Shu-Jhen Jheng; Shang-Wen Lin; Hua-Lin Wu; Jui-Chen Tsai (MDPI AG, 2021)
Recombinant human thrombomodulin (rhTM), an angiogenesis factor, has been demonstrated to stimulate cell proliferation, keratinocyte migration and wound healing. The objective of this study was to develop nanostructured lipid carrier (NLC) formulations encapsulating rhTM for promoting chronic wound healing. RhTM-loaded NLCs were prepared and characterized. Encapsulation efficiency was more than 92%. The rate of rhTM release from different NLC formulations was influenced by their lipid compositions and was sustained for more than 72 h. Studies on diabetic mouse wound model suggested that rhTM-NLC 1.2 µg accelerated wound healing and was similar to recombinant human epidermal growth factor-NLC (rhEGF-NLC) 20 µg. By incorporating 0.085% carbopol (a highly crosslinked polyacrylic acid polymer) into rhTM NLC, the NLC-gel presented similar particle characteristics, and demonstrated physical stability, sustained release property and stability within 12 weeks. Both rhTM NLC and rhTM NLC-gel improved wound healing of diabetic mice and cell migration of human epidermal keratinocyte cell line (HaCaT) significantly. In comparison with rhTM solution, plasma concentrations of rhTM post applications of NLC and NLC-gel formulations were lower and more sustained in 24 h. The developed rhTM NLC and rhTM NLC-gel formulations are easy to prepare, stable and convenient to apply to the wound with reduced systemic exposure, which may warrant potential delivery systems for the care of chronic wound patients.